The Creation Theme in the Gospel of John - Kubiś, Adam (Collectanea Theologica, 2021)
The article surveys recent scholarship on the use of creation imagery in the Gospel of John, with the aim of presenting a rather exhaustive register of possible references. Both the obvious and the less clear-cut allusions to Gen 1–3 are discussed, the main focus being to accumulate and assess the evidence (for or against) all the apparent references to creation imagery. Included in this examination are several unconvincing and even far-fetched proposals advanced by some modern scholars, in order to give the fullest possible picture of the current discourse on these issues. After discussing the creation theme in the Prologue (1:1–18), the article explores the presence of creation imagery in the Book of Signs (1:19–12:50) and the Book of Glory (13:1–21:25).